2013
DOI: 10.1371/journal.pone.0071417
|View full text |Cite
|
Sign up to set email alerts
|

Light-Intensity Physical Activity and Cardiometabolic Biomarkers in US Adolescents

Abstract: BackgroundThe minimal physical activity intensity that would confer health benefits among adolescents is unknown. The purpose of this study was to examine the associations of accelerometer-derived light-intensity (split into low and high) physical activity, and moderate- to vigorous-intensity physical activity with cardiometabolic biomarkers in a large population-based sample.MethodsThe study is based on 1,731 adolescents, aged 12–19 years from the 2003/04 and 2005/06 National Health and Nutrition Examination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
171
3
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 176 publications
(185 citation statements)
references
References 26 publications
8
171
3
3
Order By: Relevance
“…Although the relationship between physical activity and HBP has previously been discussed [16][17][18][19][20] , the largest body of evidence indicates no association between physical activity and HBP 24 . The results of the present study corroborated previous studies that indicated no association between practicing sports and HBP in young Brazilians 9,11,[21][22][23] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the relationship between physical activity and HBP has previously been discussed [16][17][18][19][20] , the largest body of evidence indicates no association between physical activity and HBP 24 . The results of the present study corroborated previous studies that indicated no association between practicing sports and HBP in young Brazilians 9,11,[21][22][23] .…”
Section: Discussionmentioning
confidence: 99%
“…
Abstract (PR = 1,60,1,52 and 1,93,1,25) and on non sport practitioners (RP = 1,80,1,14 and 2,15,1,16). For young people sports practitioners were not found associations between overweight and obesity with HBP (PR = 1,01, 0,82 and 1,09, 0,48
…”
mentioning
confidence: 94%
“…The current Canadian guidelines are based on a systematic review of the relationships between PA and health indicators in school-aged children and youth, which supported the importance of MVPA Tremblay et al 2010bTremblay et al , 2011. While the significance of MVPA cannot be overstated, this research and messaging approach has resulted in a narrow focus on 1 h of the 24-h period (<5% of each day), and emerging evidence suggests that all intensities of PA (including light-intensity physical activity; LPA) may be important for health promotion and disease prevention (Carson et al 2013). …”
Section: Introductionmentioning
confidence: 93%
“…4/15 studies reported mixed favourable and null associations Belcher et al 2010;Kelly et al 2010;Jimenez-Pavon et al 2013c) 1/15 studies reported mixed null and unfavourable associations ) MVPA: 20/30 studies reported favourable associations (Ekelund et al 2004;Lohman et al 2006;Ness et al 2007;Stevens et al 2007;Mark and Janssen 2009;Riddoch et al 2009;Steele et al 2009;Belcher et al 2010;Martinez-Gomez et al 2010b;Holman et al 2011;Grydeland et al 2012;Lawman et al 2012;Carson et al 2013;Ekstedt et al 2013;Jimenez-Pavon et al 2013a;Taverno Ross et al 2013;da Silva et al 2014;Young et al 2014;Katzmarzyk et al 2015aKatzmarzyk et al , 2015b) 6/30 studies reported mixed favourable and null associations Peart et al 2011;Ruiz et al 2011;Mendoza et al 2012;St George et al 2013;Jimenez-Pavon et al 2013c) 3/30 studies reported null associations (Hurtig-Wennlof et al 2007;Ortega et al 2007;Martinez-Gomez et al 2012) 1/30 studies reported mixed null and unfavourable associations (Mark and Janssen 2009;Holman et al 2011) 3 studies examined bouts of MVPA and associations were favourable (2/3 studies; Holman et al 2011;da Silva et al 2014) or mixed (favourable and null; 1/3 studies; Mark and Janssen 2009) MPA: 2/10 studies reported favourable associations …”
Section: No Serious Imprecisionmentioning
confidence: 99%
“…From a preventive health perspective, the potential of breaking up sitting time and increasing time spent in light-intensity physical activity has emerged as a compelling opportunity to make a practicable and meaningful impact on population activity levels [15,[80][81][82]. On average, MVPA occupies only a few minutes of many adults waking days, thus it has limited potential to displace sedentary time (see Fig.…”
Section: An Ecological Perspective On Changing Sedentary Behavioursmentioning
confidence: 99%